2018
DOI: 10.18632/oncotarget.25139
|View full text |Cite
|
Sign up to set email alerts
|

FSH receptor binding inhibitor impacts K-Ras and c-Myc of ovarian cancer and signal pathway

Abstract: The present study aimed to investigate FSHreceptor binding inhibitor (FRBI) effects on relative factors (K-Ras, c-Myc and Vascular endothelial growth factor (VEGF)) to ovarian cancer, and expression levels of FSH receptor (FSHR) mRNAs and proteins in the cumulus-oocyte complex (COCs), to determine changes of protein kinase A (PKA) in sheep granulosa cells, further to elucidate signaling pathway of FRBI action. COCs were cultured in vitro for 24h under supplementation of varying concentrations of FRBI (0, 10, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Interestingly, PSPO2 is known to play an important role in ovarian follicular growth (Bouilly et al 2017) and is involved in some developmentally related signaling pathways (Dong et al 2017;Ilmer et al 2015). In addition, FSH genetic variations have been associated with genital lesions and infertility in males (André et al 2018;Tamburino et al 2017) as well as with ovary and various female gonad developmental processes (Wei et al 2018). Therefore, the significantly higher expression levels of these two genes in IG pituitary tissues are insufficient to explain the molecular mechanism of intersexual goats, but they may be involved in the maintenance of the physiological phenotype and biological regulation of intersexual goats.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PSPO2 is known to play an important role in ovarian follicular growth (Bouilly et al 2017) and is involved in some developmentally related signaling pathways (Dong et al 2017;Ilmer et al 2015). In addition, FSH genetic variations have been associated with genital lesions and infertility in males (André et al 2018;Tamburino et al 2017) as well as with ovary and various female gonad developmental processes (Wei et al 2018). Therefore, the significantly higher expression levels of these two genes in IG pituitary tissues are insufficient to explain the molecular mechanism of intersexual goats, but they may be involved in the maintenance of the physiological phenotype and biological regulation of intersexual goats.…”
Section: Discussionmentioning
confidence: 99%
“…Among multiple malignancies, such as breast cancer, prostate cancer, lung cancer, and ovarian cancer, excessive activation of c-Myc is thought to be involved in tumorigenesis and tumor development 36. The overexpression of c-Myc protein is likely to promote the process of malignancy and tumor progression 37. High c-Myc expression is associated with high recurrence, poor overall survival, and cisplatin resistance in these patients with high-grade serous ovarian cancer 38.…”
Section: Discussionmentioning
confidence: 99%
“…Their expression levels are correlated to carcinogenesis of ovarian and gynecologic cancers (6). There is little information regarding the influence of FRBI on ARID1A, PTEN, and FSHR associated with ovarian cancers (21,22) and no quantitative research has been reported about the correlation between ovarian carcinogenesis and levels of ARID1A and PTEN in humans and animals (1,23).…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with an earlier report (9). Therefore, FRBI, as a novel biomarker, could be utilized for early diagnosis and therapy of ovarian cancers (22). The actual effects of FRBI on anticancer activity and progression of ovarian cancers will need to be thoroughly investigated in the future (1).…”
Section: Discussionmentioning
confidence: 99%